First record of Pagellus bellottii (Teleostei: Sparidae) in the Bay of Biscay, France. Issue 1 (December 2016) - Iglésias, Samuel; Lorance, Pascal
Abstract The red pandora, Pagellus bellottii, is a tropical and subtropical demersal porgy (Sparidae) distributed in the eastern Atlantic, mostly along African coast. Several recent records in the Gulf of Cádiz suggests a northward migration of the species. Two specimens of the red pandora were caught in the southeast Bay of Biscay during the 2014 French fishery survey programme. They represent the first records of the species for the Bay of Biscay and for French waters. In Europe the species has been previously recorded only in the Gulf of Cádiz in the Atlantic and in Spanish Mediterranean waters. The hypothesis that global climate change is a factor for this almost 7° northward species range extension, commonly distributed in the tropical and subtropical eastern Atlantic along the African coast, is analysed using temperature data from the World Ocean Atlas 2013. The northern extension of the distribution range ofPagellus bellottii most probably is a consequence of the warming waters of the Bay of Biscay over the past decades.